Unveiling the mechanisms of ultrasonic radiation-induced free radical stress on algal communities: Insights into growth inhibition, photosynthetic disruption, and antioxidant defense responses - Xiaoge Wu; Tingting Shen; Xiaoyang Liu; Guangming Zhang; Xiaoqing Qian; Wenlan Yang (Ultrasonics Sonochemistry)
Algal blooms pose a significant threat to global environmental health, compromising water quality and public safety. Ultrasonic radiation has emerged as a promising, eco-friendly strategy for controlling these blooms, but the underlying mechanisms remain unclearly understood. This study investigated the effects of ultrasonic radiation on the growth, photosynthetic performance, and antioxidant defense systems of an algal mixture over a 5-day period. Analysis techniques, including scanning electron microscopy (SEM), excitation-emission matrix (EEM) analysis, and transcriptomic profiling, were employed to elucidate the multifaceted responses of algal cells to ultrasonic treatment. Ultrasonic radiation induced significant free radical generation, primarily hydroxyl radicals (·OH), which played a critical role in cellular damage. Within 24 h, treatment led to a 50% reduction in algal cell counts, a 30% decline in chlorophyll-a levels, and a 25% decrease in photosynthetic efficiency. Phycocyanin, a vital pigment for cyanobacteria, exhibited heightened sensitivity to a single ultrasonic treatment, while subsequent treatments showed no additional reduction, suggesting that Microcystis aeruginosa is particularly susceptible to the ultrasonic damage. EEM analysis revealed significant changes in the fluorescence intensity of extracellular organic matter (EOM) and intracellular organic matter (IOM) peaks, indicative of oxidative stress and metabolic disruption. Transcriptomic analysis of Microcystis aeruginosa revealed a profound reprogramming of gene expression in response to sonication. Stress response genes, particularly those involved in antioxidant defense, were upregulated, while photosynthesis-related genes were downregulated. Our research indicates that short-term ultrasonic radiation has a long-term stress effect on algal cells, and this might be able to prevent the tendency of cyanobacteria blooms.